Breeding cassava and sweet potato for pest and disease resistance in Africa - Hahn, S.K.; Caveness, F.E.; Lema, K.M.; Theberge, R.L. (1990)
IITA's research in breeding cassava and sweet potato for resistance to pests and diseases of major economic importance in Africa is discussed under the headings: breeding cassava for resistance to pests (cassava green spider mite (Mononychellus progresivus and M. tanajoa) and cassava mealybug (Phenacoccus manihoti)); breeding cassava for resistance to disease (African cassava mosaic geminivirus, cassava bacterial blight (Xanthomonas campestris pv. manihotis) and cassava anthracnose disease (Colletotrichum gloeosporioides f.sp. manihotis)); and breeding sweet potato for resistance to sweet potato virus, weevils and nematodes and integrated control of nematodes.